Covert Action, Hidden Influence: American Hegemony and the Coup d'Etat, 1946-2002. - Sydor-Estable, Nikola (Université d'Ottawa | University of Ottawa, 2011)
This paper uses the concept of hegemony to situate coups d’etat within a neo-Gramscian theoretical framework. Through a review of the relevant theoretical literature on hegemony and research on coups d’etat, and drawing heavily on the documented American uses of covert action to promote coups in Iran, Guatemala and Chile, the paper identifies a number of channels of American hegemonic influence relevant to coups d’etat and proposes several independent variables to capture these channels of influence: trade, military transfers, military aid, and political openness. The extent of American military aid to a country is found to have a statistically significant and positive impact on alignment following a coup. The duration of American military-to-military contact through arms transfers is generally found to have a statistically significant impact on the likelihood that a coup d’etat will be attempted, and on the likelihood of a successful coup d’etat in countries that are identified as having an anti-American alignment. Conversely, these variables are found to have no statistically significant impact on the likelihood of either a coup attempt or a durable coup in countries that are identified as having a pro-American alignment. These results are consistent with the neo-Gramscian hypotheses of coups that are developed in this paper. An appendix is also included that details a method for adjusting data from the Affinity of Nations index to better reflect alignment in the context of global trends in measured affinity with the United States.